PENERAPAN SANKSI PIDANA DI BAWAH ANCAMAN MINIMUM DALAM PERKARA TINDAK PIDANA KORUPSI - Wahyuni, Wahyuni (Katalogis, 2017)
This research aimed at determining of criminal sanctions lower than special minimum penalty of crime in corruption cases as provided in the prevailing laws was clearly inconsistent as the principle of nullapoena sine lege (no crime without law), implied that the judges were prohibited to break the provisions clearly set forth in laws, incluiding but not limited to minimum penalty of crime as set forth in Corruption Law. One of the ratios of the establishment of legal principle was that a judge is not authorized or prohibited to sentence penalty of crime beyond the limit provided in the laws. The considerations of judge to impose criminal sanctions lower than special minimum penalty for corruptions was to secure justice among the corruptors, people and country. The Judge relied his sentence based on legal facts exposed in the proceedings in the line with the intention or delibration of the corruptors, the nature of the corruptive actions, value of loss to the nations an the degree to which the corruptors recover the loss of the nations.Â